Boxer safety, and the relationship between the referee and the ringside physician - Sethi, N K (South African Journal of Sports Medicine, 2015)
Both the referee and the ringside physician are entrusted with the safety of the boxer in the ring. The Uniform Boxing Rules (approved August 25, 2001, Amended August 2, 2002, Amended July 3, 2008) recognise the referee as the sole arbiter of a bout and the only individual authorised to stop a contest. Unified rules of mixed martial arts (MMA) and some boxing commissions recognise both the referee and the ringside physician as arbiters of a fight, and the only individuals authorised to enter the fight area at any time during competition and stop a fight when the combatant’s safety is compromised. Irrespective of who stops the fight, the stoppage should be timely and fair to the combatants and their corners; a premature stoppage is unfair to the boxers, their corners, the promoter and the public, while a fight stopped too late risks serious injury and even death of the boxer.[1] Stoppage from inside the